2019
DOI: 10.24326/asphc.2019.2.22
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical and Chemical Properties of Cornelian Cherry (Cornus Mas L.) Fruits in Dependence on Degree of Ripening and Ecotypes

Abstract: Cornelian cherry in Poland belongs to the alternative fruit species. The fruits are suitable for fresh consumption, however they can be used for processing: juice, jams, jellies, syrups, tinctures. Fruits are abundant in mineral elements, vitamin C, organic acids, iridoids, anthocyanins and due to that they have health-promoting significance. In this experiment, the fruit quality of several 16-year-old ecotypes in the Lublin region was compared. They were compared in terms of the beginning of fruit ripening an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
3
9
0
1
Order By: Relevance
“…Pericarp namely contained the most moisture at GF stage and the parameter declined with maturation. Similar findings were reported by Szot et al 20 and Yarilgaç et al 29 for Cornus mas fruit. However, GF was characterized by significantly highest fruit firmness which decreased at later maturity stages.…”
Section: Morphological Traitssupporting
confidence: 91%
See 3 more Smart Citations
“…Pericarp namely contained the most moisture at GF stage and the parameter declined with maturation. Similar findings were reported by Szot et al 20 and Yarilgaç et al 29 for Cornus mas fruit. However, GF was characterized by significantly highest fruit firmness which decreased at later maturity stages.…”
Section: Morphological Traitssupporting
confidence: 91%
“…Fruit length and width (maximum diameter of the equatorial section) were measured with a digital caliper (sensitivity 0.01 mm) on ten fruit per branch on each sampling. Fruit shape index was calculated according to the formula I = length 2 /width 2 20 . Fruit mass (sensitivity 0.0001 g) of ten fruit (two from each branch) was also recorded immediately after transport to the laboratory on each sampling date and relative water content was calculated by comparing the weight of lyophilized samples as reported previously by Cunja et al 21 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies conducted with cornelian cherry fruits, Tural and Koca 2008 Considering the bioactive components of the genotypes, it was observed that yellow fruits generally had lower antioxidant activity and total phenolics; there were significant variations among the genotypes and present values were mostly greater than earlier reports. Although the differences are thought to be mainly caused by the variation of the examined varieties, differences in climate and soil characteristics, the geographical situation of the area where the cultivation is made, the type and time of harvest, the storage or processing of the crop, the method or periodic differences of the applied cultural processes, crop load, tree ages and fruit ripening levels cause significant differences on the final form and the amount of the phytochemical composition (Benvenuti et al, 2004;Yılmaz et al, 2009;Ercisli et al, 2011;Gündüz et al, 2013;Ersoy et al, 2018b;Sochorova et al, 2019;Szot et al, 2019b;Bolat and Ikinci, 2020;Mertoglu et al, 2020).…”
Section: Genotypesmentioning
confidence: 99%